PENGARUH KEPEMIMPINAN KEPALA MADRASAH, PENGEMBANGAN, BUDAYA KERJA DAN SELF LEARNING TERHADAP KOMPETENSI PEDAGOGIK GURU MADRASAH ALIYAH NEGERI (MAN) DI KAWASAN PESISIR PANTAI UTARA JAKARTA - Sintha Wahjusaputri (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
The purpose of this study was to determine the effect of madrasah principal’s leadership, development, work culture, and self learning on competence of pedagogic teacher performance Madrasah Aliyah Negeri at The Northern Coast of Jakarta. This research tried to answer problems about competence of pedagogic teacher performance with evidence increasing of learning quality. The research was conducted on competence of pedagogic teacher performance involving samples of 70 teacher had been selected from the target population of 85 teacher by using quantitative approach with path analysis methodes. The research of the hypothesis testing show: (1) leadership had a direct effect positive on competence of pedagogic; (2) development had a direct effect positive on competence of pedagogic; (3) self learning had a direct effect positive on competence of pedagogic; (4) leadership had a direct effect positive on self-learning; (5) development had a direct effect positive on self-learning; (6) work culture had a direct effect positive on self learning; (7) leadership had a direct effect positive on work culture; (8) development had a direct effect positive on work culture. Therefore to improve the competence of pedagogic teacher performance Madrasah Aliyah Negeri, need to increase leadership, development, work culture and self learning. Keywords: Leadership, Development, Work Culture, Self Learning, and Pedagogic Competence.